Five-year costs from a randomised comparison of bilateral and single internal thoracic artery grafts. Issue 16 (4th April 2019) - Little, Matthew; Gray, Alastair; Altman, Doug; Benedetto, Umberto; Flather, Marcus; Gerry, Stephen; Lees, Belinda; Murphy, Jacqueline; Campbell, Helen; Taggart, David
Abstract : Background: The use of bilateral internal thoracic arteries (BITA) for coronary artery bypass grafting (CABG) may improve survival compared with CABG using single internal thoracic arteries (SITA). We assessed the long-term costs of BITA compared with SITA. Methods: Between June 2004 and December 2007, 3102 patients from 28 hospitals in seven countries were randomised to CABG surgery using BITA (n=1548) or SITA (n=1554). Detailed resource use data were collected from the initial hospital episode and annually up to 5 years. The associated costs of this resource use were assessed from a UK perspective with 5 year totals calculated for each trial arm and pre-selected patient subgroups. Results: Total costs increased by approximately £1000 annually in each arm, with no significant annual difference between trial arms. Cumulative costs per patient at 5-year follow-up remained significantly higher in the BITA group (£18 629) compared with the SITA group (£17 480; mean cost difference £1149, 95% CI £330 to £1968, p=0.006) due to the higher costs of the initial procedure. There were no significant differences between the trial arms in the cost associated with healthcare contacts, medication use or serious adverse events. Conclusions: Higher index costs for BITA were still present at 5-year follow-up mainly driven by the higher initial cost with no subsequent difference emerging between 1 year and 5 years of follow-up. The overall cost-effectiveness of the two procedures, to be assessed at the primary endpoint of the 10-year follow-up, will depend on composite differences in costs and quality-adjusted survival. Trial registration number: ISRCTN46552265